39th AIAA Fluid Dynamics Conference 2009
DOI: 10.2514/6.2009-3714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Micro-Ramps on a Shock Wave/Turbulent Boundary Layer Interaction

Abstract: Stereoscopic particle image velocimetry is used to investigate the effects of micro-ramp sub-boundary layer vortex generators, on an incident shock wave/boundary layer interaction at Mach 1.84. Single-and double-row arrangements of micro-ramps are considered. The micro-ramps have a height of 20% of the unperturbed boundary layer thickness and the measurement planes are located 0.1 and 0.6 boundary layer thicknesses from the wall. The micro-ramps generate packets of individual vortex pairs downstream of their v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 30 publications
3
49
1
Order By: Relevance
“…Sun et al [16] measured the three-dimensional structure of K-H vortices using tomographic PIV (Tomo-PIV). The experiments returned more an arch-like vortex rather than full ring or hairpin, which stands in some contrast to the work of Li & Liu [14] and Blinde et al [13], respectively. More in particular, the discrepancy with the vortex ring model has not been reconciled so far and motivates the present study.…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Sun et al [16] measured the three-dimensional structure of K-H vortices using tomographic PIV (Tomo-PIV). The experiments returned more an arch-like vortex rather than full ring or hairpin, which stands in some contrast to the work of Li & Liu [14] and Blinde et al [13], respectively. More in particular, the discrepancy with the vortex ring model has not been reconciled so far and motivates the present study.…”
Section: Introductioncontrasting
confidence: 53%
“…From the unsteady behavior of the wake, the clearest feature emerging from both experiments and simulations is the vortex shedding from the quasi-circular free shear layer emanating from the ramp trailing edge. Blinde et al [13] inferred this from the wall-normal counter-rotating vortex pairs from the stereoscopic particle image velocimetry (Stereo-PIV) analysis in planes parallel to the wall. The numerical study of Li & Liu [14] showed that those vortices were rolled up from the growth of Kelvin-Helmholtz (K-H) shear layer instability and finally developed into ring-shaped vortices.…”
Section: Introductionmentioning
confidence: 99%
“…The main motivation behind applying any flow control effort is to reduce the detrimental effects of flow separation or compressible mixing with the intention of improving the overall performance. The first and foremost step in this direction lies in altering the characteristics of the incoming boundary layer by adding energy to its mean velocity profile [10]. By doing so, the resulting relatively more energetic boundary layer becomes more resistant to conditions imposed by the adverse pressure gradient, which helps to reduce the overall extent of the separation and the associated flow unsteadiness.…”
Section: Introductionmentioning
confidence: 99%
“…However, active flow control devices, as already mentioned before, can be complex, expensive and also difficult to implement and maintain [25]. Various groups in USA [29][30][31][32][33], Europe [10,28,34,35], UK [26,27], India [36,37] and China [38] are looking at different methods of shock-induced control in various areas of research applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation